Evaluation of the efficacy of the antimicrobial peptide HJH-3 in chickens infected with Salmonella Pullorum - Xu, Yanzhao; Wang, Qing; Dong, Mengmeng; Song, Huishuai; Hang, Bolin; Sun, Yawei; Zhang, Huihui; Hu, Jianhe (Frontiers in Microbiology, 2023)
As a promising substitute for antibiotics, increasing attention has been given to the clinical application of antimicrobial peptides (AMPs). In this study, the mode of action of the HJH-3 against Salmonella Pullorum was investigated. The structure and properties of HJH-3 were examined in silico, and minimum inhibitory concentrations (MICs) were determined to evaluate its antimicrobial spectrum. The time-kill kinetics of HJH-3 was determined. The hemolytic activity of HJH-3 was determined by measuring the hemoglobin ultraviolet absorption value, and the cytotoxicity was determined using a CCK-8 kit. The protective effect of HJH-3 on chickens infected with S. Pullorum was evaluated in vivo. The results demonstrated that HJH-3 exhibited strong antibacterial activity against Gram-negative pathogens at MIC values of 1.5625–25 μg/mL and against Gram-positive pathogens at MIC values of 25–50 μg/mL. HJH-3 also showed activity against the Candida albicans (100 μg/mL) and Bacillus subtilis (6.25–12.5 μg/mL). HJH-3 at 100 μg/mL completely killed S. Pullorum after co-incubation for 6 h. Likewise, the hemolysis rate of CRBCs treated with 100 μg/mL HJH-3 (7.31%) was lower than that of CRBCs treated with 100 μg/mL pexiganan (40.43%). Although the hemolysis rate of CRBCs treated with 400 μg/mL HJH-3 was increased to 13.37%, it was much lower than that of 400 μg/mL pexiganan (57.27%). In regards to cytotoxicity, HJH-3 had almost no-effect on the CEF proliferation, pexiganan decreased CEFs proliferation from 56.93 to 31.00% when increasing the concentration from 50 to 200 μg/mL. In a chicken infection model, the results showed that the antibiotic prevention and HJH-3 prevention groups exhibited the best treatment effect, with the chickens being protected from the lethal dose of S. Pullorum, a decreased number of bacteria in the blood and spleen, and less pathological changes in intestinal segments. The prevention of infection by HJH-3 was similar to that by Ampicillin; the effect of treatment after infection was lower than that of treatment before infection, and the survival rate of infected chicks treated with HJH-3 was 70%, which was still higher than that of the infected chickens. These results suggest that HJH-3 has good clinical application potential and can be used as a substitute for antibiotics for the prevention and treatment of S. Pullorum infection.